2007
DOI: 10.1027/1618-3169.54.4.304
|View full text |Cite
|
Sign up to set email alerts
|

Interference Produces Different Forgetting Rates for Implicit and Explicit Knowledge

Abstract: Abstract. Exposure to a repeating set of target strings generated by an artificial grammar in a speeded matching task generates both explicit and implicit knowledge. Previous research has shown that implicit knowledge (assessed via a priming measure) is preserved after a retention interval of one week but explicit knowledge (assessed via recognition) is significantly reduced ( Tunney, 2003 ). In two experiments, we replicated and extended Tunney's findings. Experiment 1 was a partial replication of the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Thus, the implicit knowledge measure was not affected by the retention interval. This particular finding replicates the findings of previous experiments with artificial grammars (Tamayo & Frensch, 2007; Tunney, 2003). Despite the fact that RTs decreased for both new and old items as a consequence of practice during T1, the RT savings of old over new items were preserved…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, the implicit knowledge measure was not affected by the retention interval. This particular finding replicates the findings of previous experiments with artificial grammars (Tamayo & Frensch, 2007; Tunney, 2003). Despite the fact that RTs decreased for both new and old items as a consequence of practice during T1, the RT savings of old over new items were preserved…”
Section: Resultssupporting
confidence: 91%
“…Previous research on the implicit learning of artificial grammars has shown that implicit and explicit knowledge may exhibit different forgetting trajectories (Tamayo & Frensch, 2007; Tunney, 2003; Tunney & Bezzina, 2007). In this context, implicit knowledge is normally assessed by priming, that is, the facilitation expressed in reaction time-savings that participants reveal when they produce sequences generated by the underlying artificial grammar.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perlman and Tzelgov (2009, Experiment 1), for instance, also used short spatial sequences (4 or 5 in length), which were clearly separated for the participants by intervening irrelevant trials. Tunney (2003; see also, e.g., Perlman & Tzelgov, 2009; Stadler, 1989; Tamayo & Frensch, 2007; Ziessler, 1998) provided one instance where start cues have also been used in a choice reaction task with a regular sequence. There, the words “START” and “END” had been inserted between sequences generated by an artificial grammar.…”
Section: Discussionmentioning
confidence: 99%
“…It is speculated that, in the current study, learning in the Word‐Alph and Word‐Arb groups may have suffered greater interference from general everyday activities of university students such as reading and attending classes, because they require item‐specific declarative learning. Studies using artificial grammar and paired associates paradigms show greater effects of retroactive interference in declarative compared with nondeclarative learning (Graf & Schacter, 1987; Tamayo & Frensch, 2007; Tunney, 2003). Finally, even if Offline improvement cannot be considered an exclusive marker of procedural learning, given the greater susceptibility of declarative learning to rapid decay and interference, procedural consolidation is more likely to manifest in Offline improvement and may thus explain the results of the current study.…”
Section: Discussionmentioning
confidence: 99%